Cost-effectiveness of pharmacotherapies for nicotine dependence in primary care settings: a multinational comparison. (25th May 2006) - Cornuz, J; Gilbert, A; Pinget, C; McDonald, P; Slama, K; Salto, E; Paccaud, F
Abstract : Objective: To estimate the incremental cost-effectiveness of the first-line pharmacotherapies (nicotine gum, patch, spray, inhaler, and bupropion) for smoking cessation across six Western countries—Canada, France, Spain, Switzerland, the United States, and the United Kingdom. Design and study population: A Markov-chain cohort model to simulate two cohorts of smokers: (1) a reference cohort given brief cessation counselling by a general practitioner (GP); (2) a treatment cohort given counselling plus pharmacotherapy. Effectiveness expressed as odds ratios for quitting associated with pharmacotherapies. Costs based on the additional physician time required and retail prices of the medications. Interventions: Addition of each first-line pharmacotherapy to GP cessation counselling. Main outcome measures: Cost per life-year saved associated with pharmacotherapies. Results: The cost per life-year saved for counselling only ranged from US$190 in Spain to $773 in the UK for men, and from $288 in Spain to $1168 in the UK for women. The incremental cost per life-year saved for gum ranged from $2230 for men in Spain to $7643 for women in the US; for patch from $1758 for men in Spain to $5131 for women in the UK; for spray from $1935 for men in Spain to $7969 for women in the US; for inhaler from $3480 for men in Switzerland to $8700 for women in France; and for bupropion from $792 for men in Canada to $2922 for women in the US. In sensitivity analysis, changes in discount rate, treatment effectiveness, and natural quit rate had the strongest influences on cost-effectiveness. Conclusions: The cost-effectiveness of the pharmacotherapies varied significantly across the six study countries, however, in each case, the results would be considered favourable as compared to other common preventive pharmacotherapies.